Implementasi Kebijakan Keterbukaan Informasi Publik pada Dinas Kominfo Kota Tasikmalaya - Tiara Indah; Puji Hariyanti (Program Studi Ilmu Komunikasi, 2018)
This study examined the implementation of public information disclosure policies carried out by the Office of Communications and Information Technology of Tasikmalaya. This research was conducted with a qualitative descriptive method. The data were taken through interviews and direct observation at the office and also on social media. This study found that the factors for successful policy implementation; ie Communication, Resource, Disposition and Bureaucratic Structure Factors are quite well fulfilled, while there are some problems; ie the lack of the number of public information service staff as the implementors of policy and of supporting facilities such as a professional camera. Despite the insufficient number of staff, the implementor able to operate the website as well as social media as a means of disseminating public information. This became one of the keys of the successful implementation of the policy so that Tasikmalaya City Communications Department rewarded as 3rd best social media category in Media Public Relation Award November 2017. Keywords: Policy Implementation, Public Information, The Government city of